«Էջմիածին» ամսագրի գեղարուեստական ձեւաւորումը (Շապիկներ եւ տիտղոսաթերթեր) - Պօղոսյան, Գայանէ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена обзору художественного оформления обложек и титульных листов официального журнала Эчмиадзинского католикосата. Обложки и титульные листы журнала «Эчмиадзин» имели цельную развитую композиционную структуру и систему декоративного иллюстрирования по традициям средневекового рукописного наследия и зодчества Армении. В данной статье рассматриваются художественные композиции внешнего оформления журнала по авторским рисункам Акопа Коджояна, Багдасара Арзуманяна, Тарагроса Тер-Варданяна и Григора Ханджяна начиная 1944—1990 гг. В разные годы художниками была установлена система иллюстрирования, соответствующая к общему идейному содержанию журнала. The article is devoted to the analysis of the artistic design of the covers and title pages of the official magazine of the Mother See of Holy Etchmiadzin. The covers and title pages of “Etchmiadzin” monthly had an integral, developed, compositional structure and decorative illustration system according to the traditions of the medieval manuscript heritage and architecture of Armenia. This article discusses the artistic composition of the external design of the magazine based on the author’s drawings of Hakob Kojoyan, Baghdasar Arzumanyan, Taragros Ter-Vardanyan and Grigor Khanjyan from 1944 up to the 1990s. Over the years, artists have established an artistic illustration system that is consistent with the general ideological content of the magazine.
Keywords: Periodicals; Drawing; Design; Illustration